Analisis Pengukuran Indeks Produktifitas Produk Tahu pada Industri Tahu di Kota Batam: Studi Kasus PT XYZ - Arsyad Sumantika; Bahariandi Aji Prasetyo (SURYA TEKNIKA, 2024)
All businesses must aim to sustain consistent success in the current industry. Increasing productivity is one approach to boost the performance of the industry. Productivity describes the efficiency and effectiveness of the company. Tofu is the main food of the Batam people, but the company's production target does not meet expectations. From August to October 2024, production output will be 1,200,000 pcs, 1,140,000 pcs, and 1,110,000 pcs, respectively, while the company's target is 1,400,000/month. This research aims to find out how productive tofu companies are in Batam City. The method used is Objective Matrix (OMAX). This method is carried out by calculating the productivity criteria ratio, determining the initial standard value and achievement target, determining the value in the body of the matrix, and calculating the productivity index. Then, the criteria were determined using 6 productivity ratios. The data was collected on the tofu machine production floor for three months, from August to October 2024. The data collection and processing results show that the total productivity index of Batam City tofu XYZ companies was at its highest point in August with an index value of 375, while in October, it was at its lowest point with an index value of 310. This shows a linear decrease in productivity. Then, the recommended solution is choosing a good supplier, regular machine maintenance, and establishing good SOPs